Safety and Outcomes of Mobile ECMO Using a Bicaval Dual-Stage Venous Catheter - D. Kanji, Hussein; Chouldechova, Alex; Harvey, Chris; O'dea, Ephraim; Faulkner, Gail; J. Peek, Giles (Asaio Journal, 2017)
There is little published data on the safety and effectiveness of mobile (inter-hospital) extracorporeal membrane oxygenation (ECMO) in adults, particularly focusing on the cannulation strategy. We sought to study the outcomes of patients cannulated with a bicaval dual lumen catheter needing mobile compared with conventional ECMO. Specifically, we evaluated the safety of using this cannulation strategy during initiation, in transport and overall performance. Multivariate adjustment was performed to report on adjusted 6 month survival as well as complications and performance from cannulation and the ECMO run. A total of 170 consecutive patients (44 mobile ECMO, 126 conventional ECMO) with severe hypoxemic respiratory failure were included in our cohort from 2010 to 2014. Improved in-hospital survival and adjusted lower 6 month mortality favored the mobile ECMO group (86% vs. 79%; odds ratio [OR] 0.24 [0.07-0.69]). Performance of ECMO and complications were similar between the two groups. There were no serious ECMO cannulation-related complications reported during cannulation and on transport. We conclude that the use of bicaval dual lumen catheters instituted with fluoroscopy guidance at referral sites is safe and should be considered in mobile ECMO patients. Furthermore, mobile ECMO is associated with an unexpected mortality benefit in severely hypoxemic patients. Further prospective study is needed to elucidate this finding.